2018
DOI: 10.1021/acs.jpca.8b10020
|View full text |Cite
|
Sign up to set email alerts
|

Tropylium and Porphyrinoid Character in Carbaporphyrinoid Systems. Relative Stability and Aromatic Characteristics of Azuliporphyrin and Tropiporphyrin Tautomers, Protonated Species, and Related Structures

Abstract: DFT studies have been carried out on 46 azuliporphyrin (AzP) and tropiporphyrin (TrP) tautomers, cations, and dications. The structures were minimized using DFT-B3LYP/6-311++G(d,p), and the relative stabilities of the tautomers for each series were computed with M06-2X and B3LYP-D3 functionals. Nucleus independent chemical shifts, both NICS(0) and NICS(1) zz , were calculated for both the center of the macrocycles and the individual pyrrolic and carbocyclic subunits. In addition, anisotropy of induced current … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 135 publications
(209 reference statements)
0
11
0
Order By: Relevance
“…It was anticipated that this factor could also play a role in altering the coordination chemistry of other carbaporphyrinoid systems such as tropiporphyrin and oxybenziporphyrin. Tropiporphyrin 7a (Figure ) is a porphyrin analogue in which a pyrrole subunit has been replaced with a cycloheptatriene ring. , The system also has global aromatic properties, although computational studies indicate that the seven-membered ring is paratropic. , Cycloheptatriene dialdehyde 34 was reacted with tripyrrane 12b in the presence of TFA under relatively dilute conditions followed by oxidation with an aqueous ferric chloride solution to give 25-methyltropiporphyrin 35 in 32% yield (Scheme ). The product proved to be somewhat unstable and prone to protonation, and the proton NMR spectrum of the free base form could only be obtained when the NMR solution was treated with potassium carbonate.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It was anticipated that this factor could also play a role in altering the coordination chemistry of other carbaporphyrinoid systems such as tropiporphyrin and oxybenziporphyrin. Tropiporphyrin 7a (Figure ) is a porphyrin analogue in which a pyrrole subunit has been replaced with a cycloheptatriene ring. , The system also has global aromatic properties, although computational studies indicate that the seven-membered ring is paratropic. , Cycloheptatriene dialdehyde 34 was reacted with tripyrrane 12b in the presence of TFA under relatively dilute conditions followed by oxidation with an aqueous ferric chloride solution to give 25-methyltropiporphyrin 35 in 32% yield (Scheme ). The product proved to be somewhat unstable and prone to protonation, and the proton NMR spectrum of the free base form could only be obtained when the NMR solution was treated with potassium carbonate.…”
Section: Resultsmentioning
confidence: 99%
“…Addition of a trace amount of TFA to a solution of 35 in CDCl 3 gave a monoprotonated species and the proton NMR spectrum (Figure 16) showed an increased diamagnetic ring current (Δδ = 15.20 ppm for 35H + compared to Δδ = 14.27 ppm in the free base form). DFT studies indicate that the sevenmembered rings in tropiporphyrin monocations are also paratropic, 51 but again the proton NMR spectra for 7H + or 35H + do not really support this suggestion. It is clear that further studies will be required to clarify these interpretations.…”
Section: ■ Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…AICD is another widely accepted visual function based on magnetic property to investigate the molecular aromaticity, which can describe the density and direction of the induced ring current in a molecule under an external magnetic field. , …”
Section: Resultsmentioning
confidence: 99%
“…42 Attempts to rationalize the conjugation pathways in terms of resonance led to the proposal of similar somewhat unlikely canonical forms, and it was concluded that azuliporphyrins cannot be satisfactorily assessed in this fashion. 51 The calculated bond lengths for the favored free-base and monocations AzC-c-22H and AzC-c-22,24H + showed very little variation for the individual bonds in the seven-membered ring apart from the position for ring fusion. In fact, this bond (C2−C3) was 0.078 Å or 0.067 Å longer, respectively, for these two species.…”
Section: ■ Results and Discussionmentioning
confidence: 99%